(untitled) (Studia Prawnicze / The Legal Studies, 2006)
W doktrynie niemieckiej w zasadzie nigdy nie ustała dyskusja nad pojęciem osoby prawnej, które było i jest analizowane nie tylko z punktu widzenia nauk prawnych, ale też socjologii, teorii organizacji czyfilozofii. Badania te stopniowo prowadzą do coraz szerszego uznania organizacji za podmioty posiadające osobowość prawną. Poniżej zostaną przykładowo wskazane podmioty nieposiadające osobowości prawnej występujące w prawie niemieckim. The study presents the situation of entities without legał personality in the German law. An association in formation (Vorvereine) is an entity which, on the base of association registration, can acąuire legał personality and become a formal association and take on rights and obligations. Association is a form used mainly for social reasons like sports, help for disabled people, literaturę, etc. Each of the members of the association has joint and several liabilities for the obligations of the association before registration (association in formation) unless a creditor acts in the justified belief that the association is registered. There are also unregistered associations which have legał capacity for certain actions but do not have a legał personality. These associations are regulated by § 54 BGB (Civil codę), the articles conceming civil partnership (§ 705 and subsequent of BGB) and the regulations applying to registered associations with legal personality. The study also describes partnerships, dividing them into civil partnerships (Gesellschaft des burgerlichen Rechts BGB-G (§ 705-740 BGB), generał partnerships (Offene Handelsgesellschaft OHG (§ 105) regulated by Commercial Code from 10 May 1897 (HGB) and limited partnerships- Kommanditgesellschaft KG (§ 161). Partnerships do not have a legał personality but, on the base on § 124 item 1 HGB, generał and limited partnerships have legał capacity. This partnership may, in its own name, acąuire rights, including the ownership of reał estates and other property rights, assume obligations, sue and be sued. These regulations are very similar to the Polish commercial codę with regard to partnerships (art. 8 § 1). In the German doctrine there is controversy conceming the definition of the third type of entity like partnerships, companies in formation or unregistered associations. In a limited partnership, at least one partner (generał partner) bears unlimited liability towards the creditors for obligations of the partnership, and at least one partner (limited partner) bears limited liability (§ 161 HGB). The act of 25 July 1994 r. regulates the Limited Liability Partnerships in German law for the Professional firms. These partnerships have legał capacity and are registered. In the case of companies in formation (in organization - Vorgesellschaft; in Grundung) the German doctrine pointed out three stages: 1) before singing the company contract (Vor-Griindungsgesellschaft), 2) company in organization af ter concluding the contract (Yorgesellschaft ) and 3) company after registration ( Gesellschaft mit beschrankter Haftung). Companies in organization have legal capacity. They may, in their own name acąuire rights (e.g. open the bank account), assume obligations. The business name of a company in organization contains the additional designation „i. G.” or in Grundung. According to the part of doctrine opinion shareholders of a company in organization are liable, jointly and severally with the company, for its liabilities up to the value of the unpaid contribution. The article also describes the situation of cooperatives in formation (Vorgenossenschaft) which exist before the cooperative registration. On the basis of registration cooperatives obtain legał personality. The study contains comparative remarks conceming Polish, French and English law in the scope of entities without legał personality.